2019
DOI: 10.1002/ijc.32106
|View full text |Cite|
|
Sign up to set email alerts
|

Insight into genetic susceptibility to male breast cancer by multigene panel testing: Results from a multicenter study in Italy

Abstract: Breast cancer (BC) in men is rare and genetic predisposition is likely to play a relevant role in its etiology. Inherited mutations in BRCA1/2 account for about 13% of all cases and additional genes that may contribute to the missing heritability need to be investigated. In our study, a well‐characterized series of 523 male BC (MBC) patients from the Italian multicenter study on MBC, enriched for non‐BRCA1/2 MBC cases, was screened by a multigene custom panel of 50 cancer‐associated genes. The main clinical‐pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 47 publications
10
62
3
1
Order By: Relevance
“…8,9,[33][34][35][36] The current analysis confirms the association with PaC and is the first in our knowledge to quantify it, with an RR estimate of 2.30 (albeit with wide confidence limits), which translates to an absolute risk of 2%-3% by age 80 years (Fig 2; Table 2). Previous studies observed a higher prevalence of PALB2 PVs in MBC, 5,[37][38][39] No previous study that we know of has demonstrated statistically significant associations of PALB2 with PrC risk, 25,[40][41][42] and our analysis points to a weak association with decreased risk. Because families were primarily ascertained through female individuals with BC and OC, this result might reflect under-reporting of PrC in these families, and the same phenomenon could explain the slightly decreased risk for all other cancers.…”
Section: Discussioncontrasting
confidence: 54%
“…8,9,[33][34][35][36] The current analysis confirms the association with PaC and is the first in our knowledge to quantify it, with an RR estimate of 2.30 (albeit with wide confidence limits), which translates to an absolute risk of 2%-3% by age 80 years (Fig 2; Table 2). Previous studies observed a higher prevalence of PALB2 PVs in MBC, 5,[37][38][39] No previous study that we know of has demonstrated statistically significant associations of PALB2 with PrC risk, 25,[40][41][42] and our analysis points to a weak association with decreased risk. Because families were primarily ascertained through female individuals with BC and OC, this result might reflect under-reporting of PrC in these families, and the same phenomenon could explain the slightly decreased risk for all other cancers.…”
Section: Discussioncontrasting
confidence: 54%
“…Over the last few years, thanks to the extensive use of NGS technology, several genes other than BRCA1/2, have been associated with increased BC/OC risk. To date, a wide range of NGS panels are available for the analysis of hereditary BC/OC [86]; generally, these panels include high-penetrance BC/OC genes (BRCA1 and BRCA2), moderate/low-penetrance genes (e.g., PALB2, CHEK2 and ATM), mismatch repair genes (e.g., MLH1 and MSH2), and genes related to hereditary cancer syndromes (e.g., CDH1, PTEN, STK11 and TP53) [87]. Overall, a critical factor for NGS panel use is that a high number of variants of unknown significance (VUS) are detected, for which clinical management is unclear.…”
Section: Pros and Cons Of Ngs Approaches For The Analysis Of Familialmentioning
confidence: 99%
“…Breast cancer (BC) and ovarian cancer (OC) are the first and the eighth most common tumors for both incidence and mortality in females, respectively [1]. BC can also affect males, even if male breast cancer (MBC) represents less than 1% of all BCs [2][3][4].…”
Section: Introductionmentioning
confidence: 99%